Canonical interpretation of Y(10750) and $$Υ (10860)$$ Υ(10860) in the $$Υ $$ Υ family - Qi Li; Ming-Sheng Liu; Qi-Fang Lü; Long-Cheng Gui; Xian-Hui Zhong (European Physical Journal C: Particles and Fields, 2020)
Abstract Inspired by the new resonance Y(10750), we calculate the masses and two-body OZI-allowed strong decays of the higher vector bottomonium sates within both screened and linear potential models. We discuss the possibilities of $$Υ (10860)$$ Υ(10860) and Y(10750) as mixed states via the $$S-D$$ S-D mixing. Our results suggest that Y(10750) and $$Υ (10860)$$ Υ(10860) might be explained as mixed states between 5S- and 4D-wave vector $$b{\bar{b}}$$ bb¯ states. The Y(10750) and $$Υ (10860)$$ Υ(10860) resonances may correspond to the mixed states dominated by the 4D- and 5S-wave components, respectively. The mass and the strong decay behaviors of the $$Υ (11020)$$ Υ(11020) resonance are consistent with the assignment of the $$Υ (6S)$$ Υ(6S) state in the potential models.